In vitro antimicrobial potential of infant mouthwashes against streptococcus mutans biofilm: A preliminary study - Glenda Guimarães Sampaio; Gabriela Leódido; Letícia Machado Gonçalves; Marco Aurélio Benini Paschoal (Wolters Kluwer Medknow Publications, 2019)
Background: Children and teenagers accumulate dental plaque easily due to immature motor coordination present at this specific age. Thus, chemical solutions such as mouthwashes are used for biofilm control. The widespread use of mouthwash could potentially change the oral environment though there is no evidence of its effects on the biofilm. Aim: The present study aimed to investigate the in vitro antimicrobial potential of infant mouthwashes on mature Streptococcus mutans biofilm. Methods: The susceptibility of S. mutans biofilm UA 159 (ATCC700610) to infant mouthwashes was tested with childrens mouthwashes containing the following active agents: G1-cetylpyridinium chloride, G2-xylitol and triclosan and G3-Malva sylvestris and xylitol. Phosphage-buffered saline (PBS) was used at the negative control (G4). In this study, cariogenic biofilm was exposed once a day for one minute to the mouthwashes over a period of five days. Following this, an aliquot of each mouthwash used was seeded in brain heart infusion (BHI) agar and then incubated at 37°C, 5% CO2 for 48 h. The results were expressed as colony-forming units (CFU) and converted into log10. The results were submitted to ANOVA and Tukey's test at 5%. Results: It was observed 7.75, 7.66, and 7.49 CFUlog10 values to G1, G2, and G3, respectively, with 9.53 CFUlog10 value to G4. Accordingly, all studied mouthwashes showed no significant statistical difference between them but with statistically significant bacterial reduction in comparison to control group. Conclusion: Infant mouthwashes presented a highly significant antimicrobial effect on cariogenic biofilm in an in vitro model, which raises concern when used by a young population.